LOXL2 promotes vasculogenic mimicry and tumour aggressiveness in hepatocellular carcinoma. Issue 2 (1st December 2018) - Shao, Bing; Zhao, Xiulan; Liu, Tieju; Zhang, Yanhui; Sun, Ran; Dong, Xueyi; Liu, Fang; Zhao, Nan; Zhang, Danfang; Wu, Lili; Wang, Yong; Wang, Meili; et al.
Abstract: Lysyl oxidase‐like 2 (LOXL2) has shown to promote metastasis and poor prognosis in hepatocellular carcinoma (HCC). Also, we have previously reported that vasculogenic mimicry (VM) is associated with invasion, metastasis and poor survival in HCC patients. In the present study, we investigated molecular function of LOXL2 in HCC and VM. We used the immunohistochemical and CD31/periodic acid‐Schiff double staining to detect the relationship between LOXL2 and VM formation. We performed the gain and loss of function studies and analysed the migratory, invasion and tube formation in HCC cell lines. We analysed the function of LOXL2 in VM formation and HCC metastasis both in vitro and in vivo. We have showed that LOXL2 was overexpression in HCC and was positively correlated with tumour grade, metastasis, VM formation and poor survival in 201 HCC patients. Secondly, our studies have showed that LOXL2 overexpression in HCC cells significantly promoted migration, invasion and tube formation. Finally, we found that LOXL2 may increase SNAIL expression, thereby enabling VM. Our study indicated that LOXL2 may promote VM formation and tumour metastasis by collaborating with SNAIL in HCC. What's more, the overexpression of LOXL2 indicated a poor prognosis in HCC patients.